Co-exploring the Water-Energy-Food Nexus: Facilitating Dialogue through Participatory Scenario Building - Johnson, Oliver W.; Karlberg, Louise (Frontiers in Environmental Science, 2017)
The ‘water-energy-food (WEF) nexus’ has become an increasingly popular way to frame the challenges associated with reconciling improvements in human wellbeing and aspirations for better lives with sustainable management of natural resources and ecosystems. Yet the nexus is complex, requiring effective engagement between expert and non-expert stakeholders in order to understand biophysical inter-linkages between resources and resource flows and social interactions between different actors in the socio-ecological system and landscape. This can be a substantial challenge due to varying levels of knowledge and understanding amongst actors with divergent, and often entrenched, interests. This paper presents insights on how participatory scenario-building processes can create space for dialogue amongst stakeholders with differing knowledge, experience, priorities and political perspectives. Drawing on completed and on-going research applying a ‘nexus toolkit’ in Ethiopia and Rwanda respectively, we contribute to a generalized conceptual framework for addressing, communicating, and assessing the water-energy-food nexus, with a particular focus on how to utilize the nexus concept in practice. We find that participatory scenario-building processes that facilitate engagement beyond technical aspects to include social, economic and political concerns provide a valuable space for discussing and negotiating development pathways that are sustainable both biophysically and socio-economically. In addition, the involvement of stakeholders throughout the project process greatly enhances the quality and legitimacy of results. Furthermore, we suggest that by building capacity amongst stakeholders to maintain a quantitative ‘nexus toolkit’, it has a better chance of informing decision-making and for supporting the development of more technically refined analyses of alternative decisions and management strategies.